From Architectured Materials to the Development of Large-scale Additive Manufacturing - Justin Dirrenberger (Spool, 2017)
Architectured materials are a rising class of materials that bring new possibilities in terms of functional properties, filling the gaps and pushing the limits of Ashby’s materials performance maps [1]. Capitalizing on the concepts of architectured materials, explorations of the potential applications of large-scale 3D printing techniques to civil engineering structures were recently implemented in the DEMOCRITE project.